(untitled) (قضايا سياسية, 2022)
The middle class is a wide non consistent mixture consist of individuals and groups that its position allowed for them to access political and cultural work and it was described as "Democracy Yeast " because it contribute in building a democratic society .As the matte concerning Iraq this class becomes a class that belongs to the state government .Although the feeling of optimism that dominate Iraq after 2003 but this class has no role in building Iraqi democratic society because of a bad political , economic and cultural conditions but creating the conditions and necessities to establish democratic society still subjected to the change in political , economic and cultural conditions for the interest of raise , building and a role for middle class again .